Ancient DNA reveals complexity in the evolutionary history and taxonomy of the endangered Australian brush-tailed bettongs (Bettongia: Marsupialia: Macropodidae: Potoroinae) - Haouchar, D.; Pacioni, C.; Haile, J.; McDowell, M.; Baynes, A.; Phillips, M.; Austin, J.; Pope, L.; Bunce, Michael (Springer, 2016)
© 2016 Springer Science+Business Media Dordrecht. The three surviving ‘brush-tailed’ bettong species—Bettongia gaimardi (Tasmania), B. tropica (Queensland) and B. penicillata (Western Australia), are all classified as threatened or endangered. These macropodids are prolific diggers and are recognised as important ‘ecosystem engineers’ that improve soil quality and increase seed germination success. However, a combination of introduced predators, habitat loss and disease has seen populations become increasingly fragmented and census numbers decline. Robust phylogenies are vital to conservation management, but the extent of extirpation and fragmentation in brush-tailed bettongs is such that a phylogeny based upon modern samples alone may provide a misleading picture of former connectivity, genetic diversity and species boundaries. Using ancient DNA isolated from fossil bones and museum skins, we genotyped two mitochondrial DNA (mtDNA) genes: cytochrome b (266 bp) and control region (356 bp). These ancient DNA data were combined with a pre-existing modern DNA data set on the historically broadly distributed brush-tailed bettongs (~300 samples total), to investigate their phylogenetic relationships. Molecular dating estimates the most recent common ancestor of these bettongs occurred c. 2.5 Ma (million years ago), which suggests that increasing aridity likely shaped their modern-day distribution. Analyses of the concatenated mtDNA sequences of all brush-tailed bettongs generated five distinct and well-supported clades including: a highly divergent Nullarbor form (Clade I), B. tropica (Clade II), B. penicillata (Clades III and V), and B. gaimardi (Clade IV). The generated phylogeny does not reflect current taxonomy and the question remains outstanding of whether the brush-tailed bettongs consisted of several species, or a single widespread species. The use of nuclear DNA markers (single nucleotide polymorphisms and/or short tandem repeats) will be needed to better inform decisions about historical connectivity and the appropriateness of ongoing conservation measures such as translocations and captive breeding.